Price Negotiation with Merchant Heterogeneity in the Payment Card Industry - Ho, Chun-Yu; Xu, Li; Zhang, Daiqiang (The Review of Economics and Statistics, 2022)
We examine price negotiation in the payment card industry by exploiting a unique merchant-, industry-, and city-level data set. Motivated by the substantial variation in acquirer fees and heterogeneous merchant card transactions, we use Nash bargaining to model the negotiation over the acquirer fee between an acquirer and a merchant. We find that the merchants secure a larger incremental surplus than the acquirer on average. Moreover, merchants might face upward pressure on acquirer fees as the card penetration rate rises over time, and policies that weaken the acquirer's bargaining power could relieve the upward fee pressure.